Hull Form Optimization Study Based on Multiple Parametric Modification Curves and Free Surface Reynolds-Averaged Navier–Stokes (RANS) Solver - Sung-Woo Park; Seung-Hyeon Kim; Yang-Ik Kim; Inwon Lee (Applied Sciences, 2022)
In this study, the hull form optimization process to minimize resistance of KCS (KRISO containership) at <semantics>Fn=0.26</semantics> is described. The bow hull form of KCS was modified by varying such design parameters as sectional area curve (SAC), section shape, bulb breadth, and bulb height using multiple parametric modification curves devised by the authors. The resistance performances of modified hull forms were analysed by the viscous flow Reynolds-Averaged Navier–Stokes (RANS) solver of WAVIS ver.2.2. With a view to saving computational time during iterative analyses in the optimization process, the sinkage and trim were set to the fixed values which had been obtained for the original hull form with free condition. The validity of such constant sinkage/trim was then verified by conducting analysis for the optimal hull form with free condition. Optimization to minimize the cost function of the total resistance coefficient of model <semantics>CTM</semantics> was performed by sequential quadratic programming (SQP), which is one of the gradient-based local optimization methods. Utilization of parallel computing led to the simultaneous calculation of the gradient, thereby speeding up the whole optimization process. At the design speed of 24 knots, the optimal hull yielded <semantics>CTM</semantics> reduction by 1.8%, which is extrapolated to 3.1% reduction of effective power <semantics>PE</semantics> in full scale.